Single‐level cervical disc arthroplasty in the spine with reversible kyphosis: A finite element study. Issue 2 (8th February 2022) - Hu, Xu; Jiang, Majiao; Hong, Ying; Rong, Xin; Huang, Kangkang; Liu, Hao; Pu, Dan; Wang, Beiyu
Abstract: Background: Our previous studies found the single‐level cervical disc arthroplasty (CDA) might be a feasible treatment for the patients with reversible kyphosis (RK). Theoretically, the change of cervical alignment from lordosis to RK comes with the biomechanical alteration of prostheses and cervical spine. However, the biomechanical data of CDA in the spine with RK have not been reported. This study aimed at establishing finite element (FE) models to (1) explore the effects of RK on the biomechanics of artificial cervical disc; (2) investigate the biomechanical differences of single‐level anterior cervical discectomy and fusion (ACDF) and CDA in the cervical spine with RK. Methods: The FE models of the cervical spine with lordosis and RK were constructed, then three single‐level surgical models were developed: (1) RK + ACDF; (2) RK + CDA; (3) lordosis + CDA. A 73.6‐N follower load combined with 1 N·m moment was applied at the C2 vertebra to produce cervical motion. Results: At the surgical level, "lordosis + CDA" had the greatest ROM (except for flexion) while "RK + ACDF" had the minimum ROM. However, at adjacent levels, the ROM of "RK + ACDF" increased by 4.05% to 38.04% in comparison to "RK + CDA." "RK + ACDF" had the greatest prosthesis interface stress, while the maximum prosthesis interface stress of "RK + CDA" was at least 2.15 times higher than "lordosis + CDA." Similarly, "RK + ACDF" had the greatest intradiscal pressure (IDP) at adjacent levels, while the IDP of "RK + CDA" was 1.6 to 6.7 times higher than "lordosis + CDA." At the surgical level, "RK + CDA" had the greatest facet joint stress (except for extension), which was 1.9 to 11.2 times higher than "lordosis + CDA." At the adjacent levels, "RK + CDA" had the greatest facet joint stress (except for extension), followed by "RK + ACDF" and "lordosis + CDA" in descending order. Conclusions: RK significantly changed the biomechanics of CDA, which is demonstrated by the decreased ROM and the significantly increased prosthesis interface stress, IDP, and facet joint stress in the "RK + CDA" model. Compared with ACDF, CDA overall exhibited a better biomechanical performance in the cervical spine with RK, with the increased ROM of surgical level and facet joint stress and the decreased ROM of adjacent levels, prosthesis interface stress, and IDP. Abstract : We constructed the finite element model of the cervical spine with reversible kyphosis (RK) for the first time to explore the effects of RK on the biomechanics of cervical disc arthroplasty (CDA) and investigate the biomechanical differences of single‐level ACDF and CDA in the cervical spine with RK. We found that RK significantly changed the biomechanics of CDA, which is demonstrated by the decreased range of motion (ROM) and the significantly increased prosthesis interface stress, intradiscal pressure (IDP), and facet joint stress in the "RK + CDA" model. Compared with ACDF, CDA overall exhibited a better biomechanical performance in the cervical spine with RK, with the increased ROM of surgical level and facet joint stress and the decreased ROM of adjacent levels, prosthesis interface stress, and IDP.